The Research Literacy of Professionals: Reconciling Evidence-Based Practice and Practical Wisdom - Eriksen, Andreas (Professions and professionalism, 2022)
There is widespread agreement that the art/science dichotomy is obsolete; professional practice must accommodate both experience-based judgment and evidence-based tools. However, there is little agreement on what this reconciliation entails, partly because we lack a conceptualization of the professional agency involved. What kind of intellectual ability is needed for the translation of research into practice? This article argues that we need a new conception of research literacy, where the distinct issues of application to practice are addressed. By first replacing the art/science dichotomy with a craft model of professional practice, the article explains how research literacy should be conceived as a virtue that preserves the integrity of the domain of expertise. This virtue is served by a set of sensitivities that enable professionals to embed evidence-based tools into practice in a collaborative and situationally attuned way. The craft-oriented conception of research literacy is explored with examples from medicine and teaching.